The Learning and Differentiation Shapes and Textures of Objects by Nectar Bat Party (Phyllostomidae: Anoura) (Revista Científica Ciencias Naturales y Ambientales, 2010)
During the months of July and December of 2010 nectar feeding bats were captured on both sides of the Andes in Ecuador's cloud forest, four Anoura caudifer and three Anoura geoffroyi, were tested, first to check the Learning of geometric shapes, where none of the species showed statistically significant learning, another test was a variation of 'Delayed non matching for sample' to see the curiosity about new forms, which found that nearly the same way come to previously known form as the new ones and also analyzed the preference between textures or shapes of objects in search of food, where it was found that they use both signals.
Keywords: Associative learning; law of effect; searching for objects; concepts of shapes; curiosity.